2021
DOI: 10.1111/sms.14115
|View full text |Cite
|
Sign up to set email alerts
|

Universal school‐based intervention targeting depressive symptoms in adolescents: A cluster randomized trial

Abstract: We investigated the effects of three different interventions on depressive symptoms in adolescents. As a secondary aim, we explored the mediating role of social isolation, anxiety, sleep quality, and cognitive function of the intervention effect on depressive symptoms. We conducted a cluster randomized controlled trial, in which schools were randomly assigned to 1. Doubling physical education (PE) classes (3:20 h of PE/week); 2. Workshop with the PE teachers; 3. Workshop with the PE teachers + Doubling PE clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Physical activity during PE classes can relieve fatigue and improve pleasure through neurophysiological stimulation and the brain's information processing function (i.e., cerebral cortex), so as to improve children's preparation ability for all day exercise ( 35 , 36 ). The decrease in the frequency of physical education will affect adolescents' opportunities to develop friendship and social skills, increasing the risk of depressive symptoms ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical activity during PE classes can relieve fatigue and improve pleasure through neurophysiological stimulation and the brain's information processing function (i.e., cerebral cortex), so as to improve children's preparation ability for all day exercise ( 35 , 36 ). The decrease in the frequency of physical education will affect adolescents' opportunities to develop friendship and social skills, increasing the risk of depressive symptoms ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are many factors affecting depressive symptoms, such as living conditions, life events and lifestyle factors ( 7 ). Among them, lifestyle factors, such as sleep duration, physical activity, physical education (PE) class participation, screen time and sedentary time could lead to a greater effect on depressive symptoms than previously believed ( 7 9 ). A recent meta-analysis showed that although the existing evidence base was still low, universal multi-risk lifestyle interventions may have a modest but statistically significant effect on reducing depressive symptoms ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents spend a high proportion of their waking day in schools which consequently have been identified as a cost-effective investment and key contributor to engagement in physical activity for health [10]. Due to some empirical evidence supporting the impact of typical school provision of physical education, physical activity and sports on adolescent physical activity behaviors [11][12][13][14][15][16][17], wellbeing [18][19][20][21][22][23][24][25] and health [26][27][28][29][30][31][32][33][34], various strategies have been put forward to further utilize schools as primary vehicles to promote physical activity and health. The International Society for Physical Activity and Health's (ISPAH) "Eight Investments that Work for Physical Activity" acknowledges a systems-based, whole-of-school approach to best practice and was devised in response to the both the aforementioned empirical evidence and the Global Action Plans targets to reduce physical inactivity [35].…”
Section: Introductionmentioning
confidence: 99%
“…Nationally, the prevalence of physical inactivity in the Republic of Ireland is high, with 90% of adolescents failing to reach the World Health Organization's physical activity recommendations [11]. Consequently, school environments have been promoted as key facilitators for enhancing physical activity levels in parallel with improving and maintaining the health and wellbeing of adolescents [12,13], the benefits of which are becoming evident in the literature [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The breadth and depth of provision is often determined by the resource base and ethos of schools. The literature indicates support for individual components of typical school provision of physical education, physical activity and sports to increase adolescent physical activity levels and attitudes to physical activity engagement that may predict enhanced health and wellbeing, e.g., obesity, health-related physical fitness, depression and anxiety [16,17,21,22]. However, a paucity of evidence exists that examines the impact of both multicomponent, whole school and systems-based approaches to typical school provision and the impact of different levels of such approaches on indicators of health in adolescent populations.…”
Section: Introductionmentioning
confidence: 99%